Роуз и тайна магии: [повесть] / Холли Вебб ; [перевод с английского И. С. Соколовой] - Вебб Холли (Тайны волшебников, 2017)
Цена: / Сис.шифр: 84(4/8) / Авт.знак: В 26 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44